Twofold trauma exposure – the dual function of attachment avoidance. Issue 5 (3rd September 2018) - Lahav, Yael; Siegel, Alana; Solomon, Zahava
ABSTRACT: Spouses of traumatized war veterans might suffer from distress following indirect exposure to combat and direct exposure to domestic abuse. Yet the effect of this twofold trauma exposure is far from being fully understood. Theory views attachment security as a personal resource mitigating adversity, whereas attachment insecurities intensify distress. Nevertheless, there are mixed results concerning the effects of attachment in the aftermath of trauma. Furthermore, the role of trauma exposure levels regarding the effects of attachment remains largely uninvestigated. Filling these gaps, this study assessed female military spouses 30 (T1) and 38 (T2) years after the 1973 Yom Kippur War. Direct (domestic abuse) and indirect (veteran partners' posttraumatic stress symptoms) trauma exposure, attachment, depression, and anxiety were assessed. Findings indicated an interaction between the trauma types in predicting spouses' anxiety. Domestic abuse moderated the relations between attachment and distress. Although attachment anxiety had nonsignificant effects on anxiety among low-level domestic abuse sufferers, it predicted elevated anxiety among high-level domestic abuse sufferers. Furthermore, while attachment avoidance predicted elevated distress among low-level domestic abuse sufferers, its effects dissolved or became positive in nature among high-level domestic abuse sufferers. Discussion focuses on evolutionary explanations of the functions of attachment under different conditions of threat.